The association between dietary intake of macro- and micronutrients and multimorbidity: a cross-sectional study in Cyprus - Kyprianidou, Maria; Chrysostomou, Stavri; Andreou, Kosmia; Alexandrou, Agni; Panagiotou, Rafaella; Christophi, Costas A.; Giannakou, Konstantinos (My University, 2023)
Research on the link between diet and multimorbidity is scarce, despite significant studies investigating the relationship between diet and individual chronic conditions. This study examines the association of dietary intake of macro- and micronutrients with multimorbidity in Cyprus's adult population. It was conducted as a cross-sectional study, with data collected using a standardised questionnaire between May 2018 and June 2019. The questionnaire included sociodemographic information, anthropometrics, medical history, dietary habits, sleep quality, smoking habits, and physical activity. The participants were selected using a stratified sampling method from adults residing in the five government-controlled municipalities of the Republic of Cyprus. The study included 1137 adults with a mean age of 40⋅8 years, of whom 26 % had multimorbidity. Individuals with multimorbidity consumed higher levels of sodium (P = 0⋅009) and vitamin A (P = 0⋅010) compared to those without multimorbidity. Additionally, higher fibre and sodium intake were also observed in individuals with at least one chronic disease of the circulatory system or endocrine system, compared to those with no chronic diseases in these systems (P < 0⋅05). Logistic regression models revealed that individuals with ≥2 chronic diseases compared to 0 or 1 chronic disease had higher fat intake (OR = 1⋅06, 95 % CI: 1⋅02, 1⋅10), higher iron intake (OR = 1⋅05, 95 % CI: 1⋅01, 1⋅09), lower mono-unsaturated fat intake (OR = 0⋅91, 95 % CI: 0⋅86, 0⋅96), and lower zinc intake (OR = 0⋅98, 95 % CI: 0⋅96, 0⋅99). Future research should replicate these results to further explore the intricate relationships between nutrient intake and multimorbidity. Our study's findings suggest that specific dietary components may contribute to preventing and managing multimorbidity.
Keywords: Chronic diseases; Cyprus; Diet; Multimorbidity; Nutrition